Our faults and our stars: some topics in comparative seismology - Fernando, BA (2021)
Seismology is one of the few geophysical probes which allows us to peer beneath the surface of a planet, moon, or star and map its structures and properties at a variety of scales and resolutions. This makes it a technique of enormous scientific power. Its application, however, suffers from problems of mathematical ill-posedness and poor conditioning. To alleviate some of these difficulties, we turn to computational seismic modelling.